Usefulness of Serum Calcitonin in Patients Without a Suspicious History of Medullary Thyroid Carcinoma and with Thyroid Nodules Without an Indication for Fine-Needle Aspiration or with Benign Cytology - Rosario, P. W.; Calsolari, M. R. (Hormone and Metabolic Research, 2016)
This study evaluated the usefulness of serum calcitonin (Ctn) in subjects without a suspicious history of medullary thyroid carcinoma (MTC) and with nodular thyroid disease without an indication for fine-needle aspiration (FNA) or with benign cytology. This was a prospective study that evaluated 421 patients with nodular disease without an indication for FNA and 602 patients with benign cytology. Patients with basal Ctn>10 pg/ml were submitted to calcium stimulation testing. Patients with stimulated Ctn>100 pg/ml were submitted to total thyroidectomy. Basal Ctn was<10 pg/ml in 1001 patients (97.8%). Among patients with basal Ctn>10 pg/ml, 16/22 exhibited stimulated Ctn>100 pg/ml. Two of these 16 patients had MTC. The 2 patients with MTC had undetectable basal Ctn 6 months after surgery. Using a cut-off of 30 pg/ml in women and 60 pg/ml in men for basal Ctn, the 2 cases of MTC of our series would have been identified and there would have been no false-positive case. It should be noted that 14/16 patients with stimulated Ctn>100 pg/ml were false-positive cases. Although uncommon, even subjects without a suspicious history and with nodular thyroid disease without an indication for FNA or with benign cytology can have MTC. The measurement of Ctn permits the diagnosis of these cases. Our results favor the hypothesis that basal Ctn could be superior to stimulated Ctn.
Keywords: serum calcitonin; thyroid nodule; medullary thyroid carcinoma